Preparation of Heterotricyclic Chlorides via Intramolecular Diels-Alder Reaction of Furans - KARAARSLAN, MUHSIN; DEMIRCAN, AYDIN (Asian Journal of Chemistry, 2010)
A variety of key precursors to the intramolecular Diels-Alder (IMDA) reaction of furan diene have been prepared via facile alkylation. Subsequently, rigid heterotricyclic chlorides 5a-e possessing oxygen, nitrogen and sulfur have been synthesized by employing a thermal IMDA reactions. Use of bulky protecting group on nitrogen 5a-b, such as t-butoxy group, can be utilized to encourage cycloaddition reactions that otherwise does not proceed.